Три погребения римских солдат из некрополя Херсонеса - Костромичёв, Д.А. (Материалы по археологии, истории и этнографии Таврии, 2005)
Мое внимание привлекли комллексы вещей трех логребений, отличающиеся необычным для Херсонесского некрололя составом. Все они расколаны Р.Х.Лелером. Описание и нумерация погребений приведены по публикации дневников раскопок некрополя. Номера в скобках соответствуют номерам полевой описи раскопок Р.Х.Лепера. The inventory of three burials excavated in Chersonesos in 1909-1910 is published in this article. All these burials were performed according to the rite of cremation. Bronze details of their belt sets mark them out of individual burials in the city necropolis. Analogies to these details are found on the territory of Roman provinces in bordering fortifications occupied by the detachments of Roman army. The burials in Chersonesos necropolis were performed during the period of the second half of the 2nd - the beginning of the Зrd centuries. It was the peak of Roman military presence in Chersonesos, which was certified m epigraphic sources. Obviously, buried people in the described graves were soldiers of the Roman army.